Faith-Based Organizations and Social Welfare: Associational Life and Religion in Contemporary Western Europe - Manuel, Paul Christopher; Glatzer, Miguel (Palgrave Studies in Religion, Politics, and Policy, 2019)
This volume examines the role and function of religious-based organizations in strengthening associational life in a representative sample of West European countries: newly democratized and long-established democracies, societies with and without a dominant religious tradition, and welfare states with different levels and types of state-provided social services. It asks how faith-based organizations, in a time of economic crisis, and with declining numbers of adherents, might contribute to the deepening of democracy. Throughout, the volume invites social scientists to consider the on-going role of faith-based organizations in Western European civil society, and investigates whether the concept of muted vibrancy aids our theoretical understanding